(untitled) - Silberman, Mel (San Francisco, 2006)
Bring out the best in yourself, your colleagues, customers, direct reports, and bosses with PeopleSmart. The ten modules in this workbook lead you through numerous activities and exercises, both independently and in groups. These modules allow you to: assess skill levels for each of the eight PeopleSmart skills, select specific job-related situations in which to improve skills, practice and apply three ways to develop each skill
Keywords: Employees,Organizational learning,Nhân viên,Tổ chức học tập; Training of,Evaluation,Sự đào tạo,Đánh giá